2005
DOI: 10.1055/s-2005-836510
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype of Down Syndrome Acute Myeloid Leukemia and Transient Myeloproliferative Disease Differs Significantly from Other Diseases with Morphologically Identical or Similar Blasts

Abstract: Immunophenotyping by the use of surface antigens and growth factor receptors is a useful tool to discriminate TMD and DS-AMKL from diseases with morphologically similar or identical blasts. The absence of EPO-R on the blast cells might be a sign of the high expression of the mutated -- and less active -- GATA1 in DS. The higher amount of CD34 co-expression in TMD may be interpreted to indicate that TMD is a slightly more immature disease than DS-AMKL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 16 publications
4
80
1
3
Order By: Relevance
“…In this study, we have labeled most DS leukemia cases as AMKL, keeping the differences in the expression of megakaryocytic and erythroid markers between DS-and non-DS-AMKL in mind, as described recently in ref. 13. We sequenced exon 2 of GATA1 from similar numbers of TMD-AMKL͞DS-AMKL and non-DS-AMKL samples (Table 4).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we have labeled most DS leukemia cases as AMKL, keeping the differences in the expression of megakaryocytic and erythroid markers between DS-and non-DS-AMKL in mind, as described recently in ref. 13. We sequenced exon 2 of GATA1 from similar numbers of TMD-AMKL͞DS-AMKL and non-DS-AMKL samples (Table 4).…”
Section: Methodsmentioning
confidence: 99%
“…An expression of either CD41, CD42 or CD61 is required for the diagnosis of AML-M7 (9,10). CD41 has also been described as a marker for TMD (7,13,29). Technical problems, including adherence of platelets to leukocytes including monocytes and blast cells can lead to false positive results for these markers (15).…”
Section: Discussionmentioning
confidence: 99%
“…Karandikar et al examined the immunophenotype of 18 patients with TMD and DS-AML and found inconclusive results for the expression of CD41 or CD61 in 4/18 cases (22%) due to background staining of neutrophil leukocytes and monocytes (16). Langebrake et al described expression of CD41 or CD61 in only 57% of TMD and 65% of DS-AML patients, Klusmann et al in 62% of TMD patients (13,25). These technical imprecisions and the lack of sensitivity for known TMD and M7 markers underlie the need for new markers in the diagnosis of these entities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recent reports showed that KIT is also expressed in almost all TL patients. 5,9 However, little is known about the expression level of KIT and the functional roles of SCF/KIT pathway in TL.…”
Section: Introductionmentioning
confidence: 99%